2014
DOI: 10.9790/2402-08918192
|View full text |Cite
|
Sign up to set email alerts
|

The Bacteriology of Fried Ready-To-Eat Foods Sold In Enugu Metropolis, Nigeria

Abstract: A research to investigate the bacteriology of four selected fried ready-to-eat food types (Yam, Potato, Akara and Plantain)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…Four (4) different ready-to-eat fried foods namely: potato, fish, bean cake and yam. The six (6) bacterial species (Tables 2 and 3) isolated from this study correlates to the reports of [30] that isolated similar organisms from fried yam, potato, bean cake and plantain sold in Enugu metropolis namely: E. coli, S. aureus, Salmonella sp, Shigella sp, Proteus sp and Klebsiella sp and Bacillus cereus. The studies of [31] documented the isolation of shiga-toxin producing E. coli from ready-to-drink milk products namely: cheese (wara) and fermented cow milk (nunu) sold in Abeokuta, Ogun State.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Four (4) different ready-to-eat fried foods namely: potato, fish, bean cake and yam. The six (6) bacterial species (Tables 2 and 3) isolated from this study correlates to the reports of [30] that isolated similar organisms from fried yam, potato, bean cake and plantain sold in Enugu metropolis namely: E. coli, S. aureus, Salmonella sp, Shigella sp, Proteus sp and Klebsiella sp and Bacillus cereus. The studies of [31] documented the isolation of shiga-toxin producing E. coli from ready-to-drink milk products namely: cheese (wara) and fermented cow milk (nunu) sold in Abeokuta, Ogun State.…”
Section: Resultssupporting
confidence: 85%
“…This, however, calls for a public health concern. The phenotypic antibiotics profile (Table 4) shows that all the isolates were 100% resistant to clindamycin and erythromycin, and 100% susceptible to nitrofurantoin which is similar to the reports of [30,29,32,33] while the multiple antibiotic resistant (MAR) index which signifies the ratio between the number of antibiotics an organism is resistant to and the total number of antibiotics it is been exposed to is presented in figure 2. It was observed that Shigella spp.…”
Section: Resultssupporting
confidence: 75%